A large cohort study of prenatal exome sequencing redefines diagnosis in fetal corpus callosum anomalies - Héron, Delphine; Gerasimenko, Anna; Frugère, Lisa; Ducourneau, Jade; Rossi, Capucine; Nava, Caroline; de Sainte-Agathe, Jean-Madeleine; Mignot, Cyril; Lehalle, Daphné; Grotto, Sarah; El-Khattabi, Laila; Nguyen, Toan; et al. (Brain (London, England : 1878), 2025)
Anomalies of the corpus callosum (AnCC) are congenital malformations associated with highly variable neurodevelopmental outcomes. We performed prenatal Exome Sequencing (pES) on a cohort of 352 fetuses diagnosed with AnCC, analyzing the diagnostic yield, the implicated genes based on the type of anomaly (partial or complete agenesis, short corpus callosum, or callosal dysgenesis) and assessing the impact on pregnancy outcomes. The overall diagnostic yield of pES was 23%, with pathogenic or likely pathogenic variants identified in 49 different genes, most of which linked to intellectual developmental disorders. The highest diagnostic yield (46%) was observed in fetuses with callosal dysgenesis. Notably, in cases of corpus callosum agenesis, variants in the DCC gene were the most frequently identified etiology (3.2%, n=9), associated with a favorable neurodevelopmental outcome. All couples with a fetal DCC variant decided to continue the pregnancy to term. In contrast, 73% of couples with other genetic diagnoses chose pregnancy termination, compared to 17% in cases without a genetic diagnosis. pES provides essential prognosis information that supports prenatal decision-making and care. The identification of genes associated with favorable outcomes, along with the integration of pES into prenatal diagnosis, enhances informed decision-making for parents and improves the clinical management of AnCC.